Congenital Pouch Colon with Double Meckel’s Diverticulum in a Patient with Persistent Cloaca - Shinde, Nand Kishor; Jhanwar, Praveen; Pant, Nitin; Choudhury, Subhasis Roy; Chadha, Rajiv (Journal of Neonatal Surgery, 2015)
Please see Fulltext